Evaluating the effects of probiotics in pediatrics with recurrent abdominal pain - Parisa Rahmani; Azin Ghouran-orimi; Farzaneh Motamed; Alireza Moradzadeh (The Korean Pediatric Society, 2020)
Background Recurrent abdominal pain (RAP) is one of the frequent complaints in general practice, particularly in pediatrics and is among the common cause of referral to gastroenterology clinics. Purpose This study is designed to investigate the effects of probiotics for the treatment of RAP and desired therapeutic outcomes. Methods One hundred twenty-five children with the diagnosis of RAP according to Rome III criteria for irritable bowel syndrome (IBS), functional abdominal pain (FAP), functional dyspepsia (FD), and abdominal migraine (AM), were enrolled in this double-blind randomized controlled trial. Results Sixty-five subjects received probiotics, and others received placebo treatment for 4 weeks. Lactobacillus reuteri was therapeutically effective in 32 patients compared to 8 patients, responding to the placebo treatment. Compared to baseline, all pain-related variables showed a significant reduction for the IBS and FD at the end of the 4th week. However, it did not respond well in FAP and AM groups. Pain-related outcomes such as, frequency of the pain, severity, and duration of the pain were decreased following the probiotic treatment. No therapeutic response was seen in AM group after the administration of probiotics. L. reuteri significantly led to pain relief in the overall population, and also in FAP, FD, and IBS subgroups. Conclusion L. reuteri probiotics are likely to lead to RAP relief and can be recommended for the treatment of functional gastrointestinal disorders.